The Theme/Motif of Death in Preschool Education - Jovana S. Milašinović (University of Belgrade, Teacher Education Faculty, 2020)
Psychological research shows that children start thinking about death, as well as developing their concepts related to it, quite early. On the other hand, there are findings indicating the ambivalent attitudes of teachers and parents when it comes to initiating conversation about death with the youngest. In this paper, we investigated the opinions of the preschool teachers about the thematization of death in preschool education and, more specifically, about the presence of literary texts with the motif of death in their work with children. A questionnaire was designed to collect the opinions of 60 preschool teachers, and the answers we obtained show, among other things, the following: a) more than a half of preschool teachers talked with children about death, b) 85% of preschool teachers had a case where a member of a child's close or extended family, or a pet, had died, c) more than a half of the preschool teachers claim that the children have shown interest in talking about death. When it comes to literary texts, it turned out that: a) preschool teachers prefer fairy tales with the motif of death over fables, even though the death of a man (even a child) occurs in them, b) that the death of the main character in a text is not an obstacle for selecting the text for teaching, c) that preschool teachers ask a wide range of questions about death related to a literary text, but also that they use questions to connect the text with the life experience of children.